Bt Brinjal impact assessment: Outcome brochure - Ahmed, Akhter; Ghostlaw, Julie (International Food Policy Research Institute, 2019)
Background Agricultural advancements have transformed Bangladesh from a food-deficit to surplus country. Now, agricultural innovations are needed to confront emerging challenges: the slowdown in agricultural growth, low agricultural diversity, the effects of climate change, and a rise in pest infestations and plant diseases, to name a few. Brinjal (eggplant) is a high-value crop widely grown and consumed in Bangladesh. Brinjal is highly vulnerable to the fruit and shoot borer pest, and farmers spray the crop heavily with pesticides. Farmers’ spending on pesticides reduces their income; and increased pesticide use heightens their risk of contracting pesticide-elated illnesses, and facing related medical costs. Developing modern, pest-resistant crop varieties can help tackle these issues. Agricultural biotechnologies such as Bt brinjal hold promise. Although the Government of Bangladesh approved cultivation of 4 Bt varieties in 2013, evidence on their potential is still lacking. What is the Bt Brinjal Study? In 2017–2018, IFPRI and the Government of Bangladesh partnered to estimate the impacts of Bt brinjal on production systems, producer welfare, and health outcomes. The study was designed by IFPRI’s Bangladesh Policy Research and Strategy Support Program (PRSSP), implemented by the Ministry of Agriculture under the Department of Agricultural Extension (DAE) and the Bangladesh Agricultural Research Institute (BARI), and coordinated by the Agricultural Policy Support Unit (APSU). Project partners regularly monitored the brinjal plots throughout the implementation period. The Bt brinjal impact assessment was supported by the Government of Bangladesh, the US Agency for International Development (USAID), the CGIAR Research Program on Policies, Institutions, and Markets (PIM), and Cornell University